THE INFLUENCE OF WORD WALL TECHNIQUE AND READING MOTIVATION TOWARD READING ACHIEVEMENT OF THE SEVENTH GRADE STUDENTS - Rini Oktarisa (Esteem Journal of English Education Study Programme, 2022)
This study aimed to finding out whether (1) there was a significant difference in reading achievement between the students who have high reading motivation taught using word wall technique and those are taught using conventional technique; (2) there was a significant difference in reading achievement between the students who have low reading motivation taught using word wall technique and those are taught using conventional technique; (3) there was a significant difference in reading achievement between the students who have high and low reading motivation taught using word wall technique and those are taught using conventional technique; (4) there was an interaction effects of word wall technique and reading motivation on the students’ reading achievementDue the research findings, it was (1) there was a significant difference in reading achievement between the students who have high reading motivation taught using word wall technique and those are taught using conventional technique (0.039<0.05). (2) there was a significant difference in reading achievement between the students who have low reading motivation taught using word wall technique and those are taught using conventional technique (.021<0.05). (3) there was a significant difference in reading achievement between the students who have high and low reading motivation taught using word wall technique and those are taught using conventional technique (.030<0.05). (4) there was an interaction effects of word wall technique and reading motivation on the students’ reading achievement (.014<0.05). it means that word wall technique is effectively used in high and low levels students’ reading motivation.